Effect of pH and Ozone Dosage on Characteristic of Ozonated Rice Bran Oil - E. Enjarlis; Marcelinus Christwardana; Sri Handayani; Sofa Fajriah; Setijo Bismo; Jehuda Reinhard Rahmani; Muhammad Tama Hazadin (Universitas Jenderal Soedirman, 2022)
The influence of pH and ozone dose, as well as ascorbic acid addition during the ozonation process, on the properties of Rice Bran Oil (RBO), was examined. The spectroscopic characteristic of RBO before and after ozonation was analysis directly, while the physicochemical property was assessed by density, viscosity, pH, iodine number, peroxide number, and acid number. With an increase in ozone dose, the carbon double bond in the RBO reduced. The primary product of the ozonation process is ozonide, and one of its by-products is 1,2,4-trioxolane, which contains a carbon single bond as a result of the ozonation reaction. According to this study, the pH 4 and ozone dose of 440 mg O3/L are the optimum parameters utilized in the RBO ozonation process. RBO's density and viscosity were 0.918 g/mL and 0.042 cP, respectively, at these conditions. Its iodine number, acid number, and peroxide number were also 3.173 g/g RBO, 2.3 mg NaOH/g RBO, and 55 mgeq/kg, respectively. Analyses of gas chromatography and nuclear magnetic resonance spectroscopy revealed the presence of 1,2,4-trioxolane. Ozone dosage is critical because greater ozone concentrations place RBO in a saturated state, making the 1,2,4-trioxolane unstable and readily destroyed, whereas lower temperatures can avoid this.